Evaluation of pulmonary sequestration with multidetector computed tomography angiography in a select cohort of patients: A retrospective study (Clinics, 2016)
OBJECTIVES: This study aimed to evaluate the role of multidetector computed tomography angiography in diagnosing patients with pulmonary sequestration. METHODS: We retrospectively analyzed the computed tomography studies and clinical materials of 43 patients who had undergone preoperative multidetector computed tomography angiography in our hospital and had pathologically proven pulmonary sequestration. Each examination of pulmonary sequestration was reviewed for type, location, parenchymal changes, arterial supply and venous drainage on two-dimensional and three-dimensional computed tomography images. RESULTS: Multidetector computed tomography successfully detected all pulmonary sequestrations in the 43 patients (100%). This included 40 patients (93.0%) with intralobar sequestration and 3 patients (7.0%) with extralobar sequestration. The locations of pulmonary sequestration were left lower lobe (28 cases, 70% of intralobar sequestrations), right lower lobe (12 cases, 30% of intralobar sequestrations) and costodiaphragmatic sulcus (3 cases). Cases of sequestered lung presented as mass lesions (37.2%), cystic lesions (32.6%), pneumonic lesions (16.3%), cavitary lesions (9.3%) and bronchiectasis (4.6%). The angioarchitecture of pulmonary sequestration, including feeding arteries from the thoracic aorta (86.1%), celiac truck (9.3%), abdominal aorta (2.3%) and left gastric artery (2.3%) and venous drainage into inferior pulmonary veins (86.0%) and the azygos vein system (14.0%), was visualized on multidetector computed tomography. Finally, the multidetector computed tomography angiography results of the sequestered lungs and angioarchitectures were surgically confirmed in all the patients. CONCLUSIONS: As a noninvasive modality, multidetector computed tomography angiography is helpful for making diagnostic decisions regarding pulmonary sequestration with high confidence and for visualizing the related parenchymal characteristics, arterial supply, and venous drainage features to help plan surgical strategies.